IMPROVEMENT OF FINANCIAL LITERACY AND DIGITAL SCHOOL FINANCIAL MANAGEMENT FOR AISYIYAH PAUD-TK TREASURERS IN SIDOARJO REGENCY - Rahmawati, Imelda Dian; Abadiyah, Rifdah (Journal of Social Comunity Services, 2026)
Objective: This community service activity aims to enhance the competence of treasurers through financial literacy training, digitization of record-keeping, and strengthening governance. Method: The methods used include training, workshops, mentoring, and evaluation. Results: The results of the activities show an increase in the treasurer's understanding of simple accounting, the ability to use financial applications, and the development of more systematic financial report standards. Novelty: TK and PAUD 'Aisyiyah, as early childhood education institutions, play a strategic role in shaping the nation's generation from an early age. In addition to academic aspects, good financial management is an important factor in supporting the sustainability of the institution. However, there are still various issues, such as the low financial literacy of treasurers, minimal digital competence, and the absence of standardized financial reports. This program is expected to enhance the transparency, accountability, and sustainability of school financial management.